A Brief Review on Fabrication of Screen-Printed Carbon Electrode: Materials and Techniques - Wahyuni, Wulan Tri; Putra, Budi Riza; Fauzi, Achmad; Ramadhanti, Desi; Rohaeti, Eti; Heryanto, Rudi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Screen-printed carbon electrode (SPCE) is one of the most interesting designs to combine a working (from carbon based material), reference, and counter electrode in a single-printed substrate. SPCE has been used in many electrochemical measurements due to its advantages for analysis in microscale. This paper summarises the main information about SPCE fabrication from the material and fabrication technique aspect on the flat substrate based on the work that has been published in the last 30 years. The success of SPCE fabrication is highly dependent on the composition of conductive ink which consists of conductive materials, binder, and solvents; substrate; and fabrication techniques. Among the carbon-based materials, the most widely used for SPCE fabrications are graphite, graphene, and carbon nanotubes. The frequent binder used are polymer-based materials such as polystyrene, polyaniline, poly 3,4-ethylenedioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyvinyl chloride. The solvents used for SPCE fabrication are varied including water and various organic solvents. The main characteristics of the SPCE substrate should be inert in order to avoid any interferences during electrochemical measurements. The screen printing and inkjet printing technique are preferred for SPCE fabrication due to easy fabrication and the possibility for mass production of SPCE.